What is the potential for a climate, forest and community friendly REDD+ in Paris? - Jonas Hein; Karen Meijer; Jean Carlo Rodríguez de Francisco (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
Reducing Emissions from Deforestation and Forest Degradation (REDD+) is a mitigation instrument that creates a financial value for the carbon stored in standing forests. The purpose of REDD+ is to provide incentives for developing countries to mitigate forest-related emissions and to foster conservation, sustainable management of forests and the enhancement of forest carbon stocks. This instrument is still not fully operational under the United Nations Framework Convention on Climate Change (UNFCCC) but, despite the large criticism it raises, its political traction is what is keeping it on the table. In this Briefing Paper, we discuss the prospects for REDD+. We structure these on the basis of options included in the Ad Hoc Working Group on the Durban Platform for Enhanced Action (ADP) Negotiating Text of February 2015: (1) forests in a market-based mechanism, (2) result-based approaches for REDD+, and (3) non-result-based approaches. In addition, we discuss for each of these the likeliness of substantial international finance that they may raise, their mitigation potential, their contribution to forest conservation, and their social co-benefits. We conclude that large sums for REDD+ can only be expected when REDD+ credits can be used to offset fossil-fuel based emissions, provided the carbon credit price is high enough. Although funds could be large, and may contribute to forest protection, there is an important counterargument: only the emissions reductions that are realised through non-offsetting approaches are net emission reductions. Integrated non-results-based approaches may offer more opportunities for local social and ecological co-benefits but it is difficult to raise funds for them. With the high stakes of protecting the global climate and important ecosystems, biodiversity and local cultures, a non-results-based mechanism seems too non-committal. But, without funds, non-offsetting approaches may not be realised at all, which may prove to be a missed opportunity for forest protection. Leakage (deforestation elsewhere) and non permanence (deforestation at a later point in time) may be an issue for all options, but form a climate risk particularly when forest credits are used to offset emissions. We suggest a middle road that focuses on regulatory measures and results-based approaches, which ensure social co-benefits, and are financed through public funds specifically generated for the purpose of developed nations assisting developing nations in adaptation and mitigation projects. Under this type of solution the results-based approach should be separated from mechanisms to reduce emissions from fossil fuel use.
Keywords: 330; Klimawandel; Landwirtschaft und ländliche Entwicklung